Possibilities of using driverless handling robots in intralogistics - Komáromi, Balázs; Szentesi, Szabolcs (Advanced Logistic Systems - Theory and Practice, 2024)
In this article we deal with production logistics within internal logistics, as well as the material supply of production, as well as the related material handling and the use of material handling robots supporting processes. Robot navigation is a multi-approach discipline that poses a major challenge in intralogistics. In general, the navigation principle, software and hardcer requirements of mobile robots must be prepared on the basis of logistics processes in such a way as to satisfy production with sufficient accuracy and safety. In the article we present the types of robots and give an insight about autonomous mobile robots.